Greenhouse gas emissions from cattle dung depositions in two Urochloa forage fields with contrasting biological nitrification inhibition (BNI) capacity - Lombardi, Banira; Loaiza, Sandra; Trujillo, Catalina; Arévalo, Ashly; Vásquez, Eduardo; Arango, Jacobo; Chirinda, Ngonidzashe (Elsevier, 2022)
Grazing-based production systems are a source of soil greenhouse gas (GHG) emissions triggered by excreta depositions. The adoption of Urochloa forages (formerly known as Brachiaria) with biological nitrification inhibition (BNI) capacity is a promising alternative to reduce nitrous oxide (N2O) emissions from excreta patches. However, how this forage affects methane (CH4) or carbon dioxide (CO2) emissions from excreta patches remains unclear. This study investigated the potential effect of soils under two Urochloa forages with contrasting BNI capacity on GHG emissions from cattle dung deposits. Additionally, the N2O and CH4 emission factors (EF) for cattle dung under tropical conditions were determined. Dung from cattle grazing star grass (without BNI) was deposited on both forage plots: Urochloa hybrid cv. Mulato and Urochloa humidicola cv. Tully, with a respectively low and high BNI capacity. Two trials were conducted for GHG monitoring using the static chamber technique. Soil and dung properties and GHG emissions were monitored in trial 1. In trial 2, water was added to simulate rainfall and evaluate GHG emissions under wetter conditions. Our results showed that beneath dung patches, the forage genotype influenced daily CO2 and cumulative CH4 emissions during the driest conditions. However, no significant effect of the forage genotype was found on mitigating N2O emissions from dung. We attribute the absence of a significant BNI effect on N2O emissions to the limited incorporation of dung-N into the soil and rhizosphere where the BNI effect occurs. The average N2O EFs was 0.14%, close to the IPCC 2019 uncertainty range (0.01–0.13% at 95% confidence level). Moreover, CH4 EFs per unit of volatile solid (VS) averaged 0.31 g CH4 kgVS−1, slightly lower than the 0.6 g CH4 kgVS−1 developed by the IPCC. This implies the need to invest in studies to develop more region-specific Tier 2 EFs, including farm-level studies with animals consuming Urochloa forages to consider the complete implications of forage selection on animal excreta based GHG emissions.